Clitoria Ternatea Floral Mediated Synthesis, Characterization, Antioxidant, and Cytotoxicity Evaluation of Silver Nanoparticles: Clitoria ternatea floral mediated SNP to control BC - Madhumitha, Hariharan; Ranjani, Soundhararajan; Karunyaa, Jenin Ravindranath; Hemalatha, Srinivasan (Archives of Breast Cancer, 2023)
Background: Green silver nanoparticles offer a reliable and secure alternative to drugs and prevent cancer. The floral part of Clitoria ternatea is traditionally well known for its application as a medicine and food in various cultures around the world. Phytochemicals of these floral extracts are enriched with various properties. Floral extracts can be utilized as an alternative that can target the proteins and other molecules involved in the progression of cancer. Methods: Silver nanoparticles (CT-AgNPs) were synthesized from the extracts of blue flowers of Clitoria ternatea (CT). The synthesized CT-AgNPs were characterized by various physicochemical methods that revealed the size, shape, and stability of the nanoparticles. Docking was performed between the phytocompounds of Clitoria ternatea and apoptotic proteins involved in breast cancer such as APAF-1, BCL-2, and BAX, to determine the ability of phytocompounds present in the floral extract to control breast cancer by binding with the targets. Results: Based on the docking results, the binding energies were ranging from -6.2 Kcal/mol to -7 Kcal/mol with Quercetin having the highest binding energies. Toxicity analysis of CT-AgNPs in Artermia nauplii and Vigna radiata seedlings confirmed that these nanoparticles were not toxic to both the model systems. Free radical scavenging activity assay revealed the antioxidant nature of CT-AgNPs were similar to that of standard ascorbic acid. In vitro cytotoxicity analysis by using MCF-7 breast cancer cell lines revealed that CT-AgNPs were cytotoxic. Conclusion: In vitro antioxidant and cytotoxicity analysis by using MCF-7 breast cancer cell lines revealed that CT-AgNPs were potent antioxidant and cytotoxic, correlating with the results of in silico analysis and hence demonstrating the anticancer potential of Clitoria ternatea floral mediated nanoparticles.